The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/jamia/ocab264
|View full text |Cite
|
Sign up to set email alerts
|

The Mass General Brigham Biobank Portal: an i2b2-based data repository linking disparate and high-dimensional patient data to support multimodal analytics

Abstract: Objective Integrating and harmonizing disparate patient data sources into one consolidated data portal enables researchers to conduct analysis efficiently and effectively. Materials and Methods We describe an implementation of Informatics for Integrating Biology and the Bedside (i2b2) to create the Mass General Brigham (MGB) Biobank Portal data repository. The repository integrates data from primary and curated data sources a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…The primary data source was the MGB RPDR, an EHR data warehouse covering 4.6 million patients across the MGB HealthCare hospital system (formerly Partners HealthCare) including Brigham & Women’s Hospital, Massachusetts General Hospital, and other affiliated hospitals in the greater Boston area. To assemble the cohort for this study, we queried the MGB RPDR for 1,546,440 patients who self-identified as non-Hispanic White (that is, 74% of the overall MGB patient population) having at least three visits after 2005, more than 30 days apart between the first and last visits, and at least one visit greater than age 10 and less than age 90, as of February 2020 (22,23) (see Figure 1 ). The race and ethnicity restriction was applied here because the subsequent PRS were based on samples of European ancestry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary data source was the MGB RPDR, an EHR data warehouse covering 4.6 million patients across the MGB HealthCare hospital system (formerly Partners HealthCare) including Brigham & Women’s Hospital, Massachusetts General Hospital, and other affiliated hospitals in the greater Boston area. To assemble the cohort for this study, we queried the MGB RPDR for 1,546,440 patients who self-identified as non-Hispanic White (that is, 74% of the overall MGB patient population) having at least three visits after 2005, more than 30 days apart between the first and last visits, and at least one visit greater than age 10 and less than age 90, as of February 2020 (22,23) (see Figure 1 ). The race and ethnicity restriction was applied here because the subsequent PRS were based on samples of European ancestry.…”
Section: Methodsmentioning
confidence: 99%
“…Each consented participant was asked to provide blood samples (e.g., plasma, serum, DNA), which are then linked to their clinical data in the EHRs as well as survey data on lifestyle, behavioral and environmental factors, and family history. Leveraging in-person and electronic recruitment methods, the MGB Biobank has currently enrolled more than 130,000 participants, collected 82,092 DNA samples, and generated genotyping microarray data for more than 56,923 participants (4,920 using the Illumina MEGA, 5,334 using the Illumina MEGA EX, 26,144 using the Illumina MEG, and 24,789 using the Illumina GSA) (23). This research was conducted as part of the PsycheMERGE Consortium (24), under approval from the MGB Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The platform has been used for a wide spectrum of use cases including clinical-trial enrollment ( Bucalo et al , 2021 ), population management ( Wagholikar et al , 2019 ), biobanking ( Castro et al , 2021 ; Mate et al , 2017 ; Segagni et al , 2011 ), clinical decision support and epidemiological analysis ( Klann and Murphy, 2013 ; Murchison et al , 2021 ; Pfiffner et al , 2016 ; Segagni et al , 2011 ; Wagholikar et al , 2017a , b ). However, despite its impact and open-source availability, the deployment of the platform is largely limited to large academic medical centers.…”
Section: Introductionmentioning
confidence: 99%
“…Data source was the Mass General Brigham (MGB) Electronic Health Records (EHR) and Biobank which stores blood samples from patients at MGB who have consented to provide samples for research purposes. 3 We identified 15 patients who received mepolizumab for the treatment of asthma and who had samples in the biobank, of whom 5 were determined to be responders to mepolizumab, and 10 were non-responders. We compared the pre-treatment serum level of each cytokine at mepolizumab initiation between responders and non-responders using moderated t-test to select top cytokines with highest differential expression between responders and nonresponders.…”
mentioning
confidence: 99%